A Prospective, Psychometric Validation of National Institutes of Health Patient-Reported Outcomes Measurement Information System Physical Function, Pain Interference, and Upper Extremity Computer Adaptive Testing in Cervical Spine Patients: Successes and Key Limitations. - Iyer, Sravisht; Koltsov, Jayme C. B.; Steinhaus, Michael; Ross, Thomas; Stein, Daniel; Jingyan Yang; LaFage, Virginie; Albert, Todd; Han Jo Kim; Yang, Jingyan; Kim, Han Jo (Spine (03622436), 2019)
Study Design: Prospective Cohort Study OBJECTIVE.: The aim of this study was to validate the Patient Reported Outcomes Measurement Information System (PROMIS) against existing patient-reported outcomes in the cervical spine.Summary Of Background Data: Current patient-reported outcomes in cervical spine have substantial limitations. PROMIS offers the potential for improved psychometric properties with reduced questionnaire burden.Methods: Adult patients undergoing cervical spine surgery at a single institution between 2016 and 2018 were prospectively enrolled. Patients completed questionnaires (36-Item Short Form Health Survey [SF-36], Neck Disability Index (NDI), Visual Analog Scale arm/neck, and PROMIS pain Interference [PI], physical Function [PF], and Upper Extremity [UE]) preoperatively and at 6 months postoperatively. Demographic data, diagnosis, and procedural data were recorded. Validation of the instruments was completed with a Rasch Model as well as measurement of coverage, efficiency, test-retest reliability, responsiveness, and convergent validity.Results: Of 197 patients who completed the preoperative survey, 164 were eligible for 6-month follow-up and 139 completed 6-month postoperative surveys. The most common diagnoses were radiculopathy (37.6%), myeloradiculopathy (30.5%), and myelopathy (28.4%). All studied instruments had acceptable fit to a Rasch model. PROMIS computer adaptive testings (CATs) demonstrated improved average time to completion for PI (39 seconds), PF (47 seconds), and UE (54  seconds), compared to NDI (117 s) and SF-36 PCS (175 seconds). Responsiveness for PROMIS CATs was similar to NDI and SF-36, test-retest reliability was lower for PI (intraclass correlation: 0.68), PF (0.70), and UE (0.59), compared to NDI (0.86) and PCS (0.85). For convergent validity, PI was strongly correlated to NDI and PF to SF-36 PCS. There were no significant floor or ceiling effects for the PROMIS domains, although UE had preoperative clustering (n = 18) at a high score (56.4) and PI had postoperative clustering (n = 27) at a low score (38.7).Conclusion: PROMIS CATs demonstrate several advantages, including efficiency and responsiveness, while demonstrating good convergent validity with legacy instruments. Nevertheless, CATs had lower test-retest reliability and had significant clustering at higher levels of function for the PI and UE CATs. These limitations must be considered before broad adoption of CATs in cervical spine patients.Level Of Evidence: 3.